Validity test of purchasing power parity doctrine: An Indonesian case study - Sahabudin Sidiq; Herawati Herawati (Universitas Islam Indonesia, 2016)
The goal of this study is to analyze the doctrine purchasing power parity (PPP) in Indonesia with the case study of the rupiah exchange rate to U.S. dollar. The autoregressive is used to estimate the relationship between the change of exchange rate and the difference Indonesia–USA inflation rate. The data used in this study are quarterly data obtained from the International Financial Statistics (IFS) and Bank Indonesia (BI) with the period 1997Q4-2013Q4. The exchange rate that used in this study is using the rate on rupiah to U S dollar. The price data used consumer price index in Indonesia and the United States with a base year of 2000. The results of this study show, that rupiah to the U.S. dollar is undervalued during the free floating exchange rate system and, the PPP doctrine to the case of the rupiah to the U.S. dollar is not valid in the period of this study.